Prevalence of Noise Induced Hearing Loss in Industrial Workers of Taxila - Farhan Ahmed, Syed Shaukat Hussain, Muhammad Aslam Khan, Mirza Nasheed Baig, Nayyer Ayub, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Occupational hazards and risks are a common public health issue, especially when healthcare workers safety is concerned; Noise induced hearing loss is a common preventable occupational hazard which affects millions of people globally1. It is the hearing loss that is caused by prolonged exposure of the ear to the noise2. Aim: To identify prevalence of Noise induced hearing loss in industrial workers from July 1, till December 31st, 2021 Study design: Descriptive, cross-sectional study Place and duration of study: The current study was conducted at Taxila at HITEC-Institute of Medical sciences from July 1, till December 31st, 2021. Methodology: A total number of 314 workers working in industrial area with noisy surroundings according to the selection criteria were included in the study. A questionnaire about past medical history of all participants in regard to ear and hearing disorders was obtained. Prevalence of NIHL was assessed in all workers with or without hearing loss. Results: The total numbers of workers included in the study were 314. The total number of patients having NIHL was 42. Prevalence of NIHL was 13. NIHL is a global health problem and is the second most important cause of hearing loss. It is a preventable disorder that affects a large proportion of workers. In our setup the NIHL was lower than expected due to better control of Noise and proper use of noise protective equipment. Keywords: NIHL = Noise-induced Hearing Loss, sensorineural hearing loss, Hearing loss.